Rajneeshpuram: inside the cult of Bhagwan and its failed American utopia - King, Russell (Chicago Review Press, 2022)
"In 1981, ambitious young Ma Anand Sheela transported the Indian guru Bhagwan Shree Rajneesh to the United States to fulfill his dream of creating a utopia for his thousands of disciples. Four years later, the incendiary Rajneeshpuram commune in Oregon collapsed under the weight of audacious criminal conspiracies hatched in its inner sanctum, including the largest bioterrorism attack in US history, an unprecedented election fraud scheme, and multiple attempted murders. RAJNEESHPURAM is a fresh examination of how this extraordinary spiritual community, featured in the Netflix docuseries WILD WILD COUNTRY, went so wrong, using newly available information and interviews with high-ranking disciples who have never before shared their stories"--